On the original relationship between Chinese and Kam-Tai - Chen, Baoya (2024)
Does Kam-Tai have any genetic relationship with Chinese? It is a key question both in Sino-Tibetan research and in Asian/Pacific language research. It is also a question involving the methodology of historical linguistics.